Ptilophora variabilis Hartig, 1968, bona species, and description of Ptilophora nebrodensis sp. n. from Sicily (Lepidoptera, Notodontidae) - Infusino, Marco; Hausmann, Axel; Scalercio, Stefano (Zootaxa, 2018)
In this paper, we redescribe Ptilophora plumigera variabilis Hartig, 1968 and raise it to species rank. Furthermore we describe Ptilophora nebrodensis sp. n. from Sicily, as the third European species belonging to the genus Ptilophora Stephens, 1828. These two species are allopatric vicariants of Ptilophora plumigera (Denis & Schiffermüller, 1775) respectively in Apennine Italy and Sicily. We present the differential features mainly concerning the morphology of genitalia and molecular data. Ptilophora variabilis shows a scattered distribution, generally very localized, whereas P. nebrodensis sp. n. is restricted to a few localities in the mountainous areas of North Sicily, being very rare. Both species predominantly inhabit forests in mountain areas, with occurrence of broadleaved trees, especially Acer spp. (Fam. Aceraceae).